Supporting 11 to 13 year old students’ reading: perceptions of parents - Nicholas, Karen; Fletcher, Jo; Parkhill, Faye (International Journal about Parents in Education, 2023)
In New Zealand, during the last decade, there has been a focus on improving home-school partnerships to help raise literacy achievement. When parents are aware of what is happening in the classroom to support their child’s reading development and learning, parents can put strategies in place to further endorse learning in the home environment. The article explores the issues surrounding the role of parents in the literacy learning of their children, particularly those of young adolescent students. Twenty seven parents of students in years seven and eight were randomly selected by the principals at six New Zealand schools. The schools represented a wide range of school types. The parents were interviewed using a semi - structured schedule. The research found that there was a link between parents who enjoyed reading and modeled this in their home environment to their child’s perceived interest and success in reading achievement. Fathers often were a powerful model for their children, more particularly their sons, when in developing attitudes towards the value and interest in reading for leisure or information.